Child Support dalam Perspektif Maqashid Syari’ah: Relevansi untuk Kasus Perceraian Modern - Fauzan Fauzan; Rizal Darwis; A. Zamakhsyari Baharuddin (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Modern divorce cases in Indonesia show a significant upward trend, with data from the Religious Courts recording 446,000 divorce cases in 2024. This phenomenon has a direct impact on the fulfillment of children's rights, particularly regarding child support, which is often understood only formally without considering the child's holistic interests. This article aims to analyze the concept of child support from the perspective of the maqasid sharia and its relevance to resolving modern divorce cases, with a focus on protecting the five main elements of maqasid. This research uses a qualitative approach with library research and analysis of court decisions. The analytical framework used is maqasid sharia, which serves as a surgical tool to evaluate existing child support practices. Research has found that child support under the Maqasid Sharia (Islamic law) is not limited to material support (food, clothing, and shelter), but encompasses the protection of five essential elements: religion (hifzh al-din), life (hifzh al-nafs), intellect (hifzh al-'aql), offspring (hifzh al-nasl), and property (hifzh al-mal). In the context of modern divorce, child support must ensure the continuity of education, psychological health, and the formation of a child's religious identity. This finding aligns with research by Zuhdi et al. (2024), which states that confiscating a husband's assets as a guarantee of child support provides benefits in the form of hifdz nafs (self-support) and hifdz aql (intellect). The Maqasid Sharia approach offers a more comprehensive and adaptive framework than the classical, textual approach of Islamic jurisprudence. This research recommends the need for Maqasid-based child support standards in the compilation of Islamic law and the strengthening of the capacity of judges and mediators in applying this approach in religious courts.